2009
DOI: 10.17221/75/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation and degeneration of domestic cat oocytes collected from ovaries stored at various temperatures

Abstract: Cat oocytes have the unique ability to mature in vitro after temporary storage at 4°C which can provide opportunities to rescue oocytes from the ovaries of endangered felids after sudden death or medical ovariohysterectomy. It has been demonstrated that factors such as season, culture conditions and morphological quality of oocytes influence the meiotic competence of domestic cat oocytes. In the present study we determined the meiotic maturation rate and incidence of apoptosis or necrosis in domestic cat oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
0
9
0
3
Order By: Relevance
“…However, only oocytes stored within the ovary for 24 h produced blastocysts, indicating that the ability to achieve nuclear maturation is an inadequate indicator of fertilization and developmental competence. Data obtained by Wlodarczyk et al (2009) indicated that storage of domestic cat ovaries at room temperature, even for a short time, can negatively influence the compe- tence of oocytes to undergo nuclear maturation. Freisted et al observed that after IVM/IVF, cleavage rates were significantly higher (P<0.05) during breeding season than during non-breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…However, only oocytes stored within the ovary for 24 h produced blastocysts, indicating that the ability to achieve nuclear maturation is an inadequate indicator of fertilization and developmental competence. Data obtained by Wlodarczyk et al (2009) indicated that storage of domestic cat ovaries at room temperature, even for a short time, can negatively influence the compe- tence of oocytes to undergo nuclear maturation. Freisted et al observed that after IVM/IVF, cleavage rates were significantly higher (P<0.05) during breeding season than during non-breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…It was only hypothesized that cytoplasmic immaturity of oocytes, chromosomal abnormalities in blastomeres and suboptimal culture conditions could cause longer intermitotic periods and, consequently, slower embryo development (Wlodarczyk et al. ; Kovacic and Vlaisavljevic ).…”
Section: Discussionmentioning
confidence: 99%
“…Esta situación se asemeja a otros estudios donde se reportaron bajas tasas de división y formación de blastocistos cuando los ovarios fueron guardados a 4 °C (Yang et al, 1990) o 10 °C (Shigeki y Yasuo, 1993, citado porWani y Nowshari, 2005). Esto puede ser posible debido a que la membrana lipídica de los ovocitos bovinos sufría cambios cuando se exponía a temperaturas inferiores a 20 °C (Arav et al, 1996); así como lesiones del huso meiótico y endurecimiento de la zona pelúcida que afectaba directamente la fecundación (Wlodarczyk et al, 2009). Sin embargo, la fase de transición lipídica no ha sido examinada para los ovocitos de alpaca.…”
Section: Discussionunclassified